Natural killer cells in highly exposed hepatitis C‐seronegative injecting drug users. Issue 6 (1st February 2016) - Mina, M. M.; Cameron, B.; Luciani, F.; Vollmer‐Conna, U.; Lloyd, A. R.; ,
Summary: Injecting drug use remains the major risk factor for hepatitis C (HCV) transmission. A minority of long‐term injecting drug users remain seronegative and aviraemic, despite prolonged exposure to HCV – termed highly exposed seronegative subjects. Natural killer (NK) cells have been implicated in this apparent protection. A longitudinal nested, three group case–control series of subjects was selected from a prospective cohort of seronegative injecting drug users who became incident cases ( n = 11), remained seronegative ( n = 11) or reported transient high‐risk behaviour and remained uninfected ( n = 11). The groups were matched by age, sex and initial risk behaviour characteristics. Stored peripheral blood mononuclear cells were assayed in multicolour flow cytometry to enumerate natural killer cell subpopulations and to assess functional activity using Toll‐like receptor ligands before measurement of activation, cytokine production and natural cytotoxicity receptor expression. Principal components were derived to describe the detailed phenotypic characteristics of the major NK subpopulations (based on CD56 and CD16 co‐expression), before logistic regression analysis to identify associations with exposed, seronegative individuals. The CD56 dim CD16 + ( P = 0.05, OR 6.92) and CD56 dim CD16 − ( P = 0.05, OR 6.07) principal components differed between exposed, seronegative individuals and pre‐infection samples of the other two groups. These included CD56 dim CD16 + and CD56 dim CD16 − subsets with CD56 dim CD16 + IFN‐ γ and TNF‐ α on unstimulated cells, and CD56 dim CD16 − CD69 +, CD107a +, IFN‐ γ and TNF‐ α following TLR stimulation. The cytotoxic CD56 dim NK subset thus distinguished highly exposed, seronegative subjects, suggesting NK cytotoxicity may contribute to protection from HCV acquisition. Further investigation of the determinants of this association and prospective assessment of protection against HCV infection are warranted.